Studi Retrospektif Kejadian Pyometra pada Pasien Kucing di Beberapa Klinik di Kota Mataram - Sofyan, Imam; Pradana, Munawer; Dharmawibawa, Iwan Doddy; Janah, Maratun (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Pyometra is a progressive and life-threatening reproductive system disease in female cats, especially those that are not sterilized. This disease is characterized by the accumulation of pus in the uterus due to a bacterial infection triggered by the influence of the hormone progesterone in the diestrus. This study aims to determine the prevalence and characteristics of pyometra cases in cats in Mataram City and identify risk factors. The research was conducted retrospectively by tracing medical record data from three veterinary clinics in Mataram City (ZZ Pet Care Clinic, Medina Vet Clinic, and drh. Rama & Partners Clinic) during the period June 2024 to May 2025. A total of 339 female cats were examined, and 42 cases of pyometra were found with a prevalence of 12.39%. The most cases were found in the age group of 1.5-2 years (52.38%) and domestic race (57.14%). All cats with the disease have not been sterilized with most having no mating history. These results show that active reproductive age, sterilization status, and local race are the main risk factors for pyometra in Mataram City. Therefore, preventive measures such as ovarihysterectomy and education to animal owners about the importance of reproductive management are needed to significantly reduce the incidence of pyometra.